2017
DOI: 10.1080/13674676.2017.1328404
|View full text |Cite
|
Sign up to set email alerts
|

Psychological type and reported religious experience: an empirical enquiry among Anglican clergy and laity

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The four dimensions of this model have been shown to relate to religious orientations in numerous studies that have examined the psychological profiles of clergy and congregations (Francis, Craig, et al, 2007;Francis et al, 2011;Francis et al, 2010;Francis & Village, 2015;Village, 2013), or individual beliefs, attitudes, and religious experiences (Francis & Village, 2017;Francis, Village, et al, 2007;Village, 2005Village, , 2010Village, , 2016. For the purposes of this paper it is relevant to point out studies that have shown connections between psychological preferences and preferences for traditional or conservative expressions of faith.…”
Section: Psychological Type and Faith Expressionmentioning
confidence: 99%
“…The four dimensions of this model have been shown to relate to religious orientations in numerous studies that have examined the psychological profiles of clergy and congregations (Francis, Craig, et al, 2007;Francis et al, 2011;Francis et al, 2010;Francis & Village, 2015;Village, 2013), or individual beliefs, attitudes, and religious experiences (Francis & Village, 2017;Francis, Village, et al, 2007;Village, 2005Village, , 2010Village, , 2016. For the purposes of this paper it is relevant to point out studies that have shown connections between psychological preferences and preferences for traditional or conservative expressions of faith.…”
Section: Psychological Type and Faith Expressionmentioning
confidence: 99%
“…The Francis Psychological Type Scales (FPTS) were created primarily in order to operationalize psychological type constructs in research (Francis, 2005). Since its release it has been widely used in questionnaire surveys, especially among religious groups (for examples see, Francis, Clymo, & Robbins, 2014;Francis, Craig, Horsfall, & Ross, 2005;Francis, Robbins, & Wulff, 2011;Francis & Village, 2017;Francis, Village, & Powell, 2019;Village, 2014Village, , 2015. The instrument consists of 10 binarychoice items related to each of the four dimensions of the psychological type models proposed by Katharine Briggs and Isabel Myers (Myers, McCaulley, Quenk, & Hammer, 1998;Myers & Myers, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Individual preferences for different psychological functions have been shown to relate to a wide range of faith expressions, including affiliation with particular types of churches (Francis 2002a;Francis et al 2007;Francis, Clymo, and Robbins 2014;Francis et al 2005;Francis and Robbins 2012;Francis, Robbins, and Craig 2011;Village 2013Village , 2015b and particular theological stances or beliefs (Francis 2002b;Francis and Village 2017;Village and Francis 2005). Two dimensions of the type model are particularly relevant for this study: perceiving (sensing versus intuition) and judging (feeling versus thinking).…”
Section: Individual Differencesmentioning
confidence: 99%